The Implementation of Audio Media Based On Scripted Songs upon the Fifth Grade Students' Competency in Primary Schools at Sub-Distric 1 Busungbiu, Buleleng in Academic Year 2014/2015 - ., I Made Pasek Suwarbawa; ., Dra.Ni Made Ratminingsih, MA; ., Dr. I Gede Budasi,M.Ed,Dip.App.Lin (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini merupakan penelitian eksperimen yang bertujan untuk menemukan efek signifikan dari pengimplementasian audio media berbasis lagu kreasi pada kemampuan kompetensi anak kelas 5 SD. Penelitian ini dilaksanakan pada Tahun ajaran 2014/2015 di Gugus 1 Kecamatan Busungbiu, Kabupaten Buleleng. Metode yang digunakan adalah metode posttest only control group, dimana dihasil akhir akan membandingkan antara nilai sumatif siswa dengan nilai posttest siswa. Hasil analisis secara deskriptif dan inferential menunjukan bahwa nilai rata-rata dari kelas eksperiment menunjukan efek yang signifikan jika disbandingkan dengan kelas control dan dukung dengan hasil t-test yang sesuai. Hasil tersebut membuktikan bahwa pengimplementasian audio media berbasis lagu kreasi memberikan signifikan efek terhadap kompetensi siswa kelas 5 SD.Kata Kunci : audio media, kompetensi, lagu kreasi This experimental study aims at finding the significant effect of Audio Media based on Scripted Songs upon the fifth grade students’ competency in primary school at Sub-District 1 Busungbiu, Buleleng in academic year 2014/2015. The design of this study was post-test only control group design. The implementation of cluster random sampling technique administrated that SD N 1 Busungbiu as experimental group which was taught by using Audio Media based on Scripted Songs and SD N 3 Busungbiu as the control group which was taught by using conventional teaching technique .Both groups consisted of 22 students each. The results of data analysis show that the students who were taught by Audio Media based on Scripted Songs performed better than those who were taught by implementing conventional teaching technique. The mean score of experimental group was 82.9 and the control group was 70.28. It was proved by the results of t-test analysis shows that the tobs was 7.793. It was higher than the value of the tcv at 2.009 (α = 0.05). In conclusion, Audio Media based on Scripted Songs gave significant effect toward students’ English competencykeyword : audio media, competency, scripted songs